2018
DOI: 10.1159/000491014
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Dialysis: Prevalence and Relationship with Uremia-Related Biochemical Parameters

Abstract: Background: Depression is the most common psychiatric disorder in long-term dialysis patients and a risk factor for morbidity and mortality. Although there is a relevance of the issue in the dialysis setting, we still know little about possible relationships between depression and uraemia-related biochemical abnormalities. Our aims were to evaluate (1) the prevalence of depression in our haemodialysis (HD) and peritoneal dialysis (PD) population using a validated and easy-to-implement screening tool and (2) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
3
11
0
1
Order By: Relevance
“…Mean patient age was 67.7 ± 14.0 years, and 44 patients were female; 78.6% of the patients were on HD, 21.4% were on PD (Table 1), 36.9% of patients presented anxious mood, and 53.6% presented depressive mood. These data were consistent to those of a previous article from our center where another screening instrument was used [14].…”
Section: Resultssupporting
confidence: 91%
“…Mean patient age was 67.7 ± 14.0 years, and 44 patients were female; 78.6% of the patients were on HD, 21.4% were on PD (Table 1), 36.9% of patients presented anxious mood, and 53.6% presented depressive mood. These data were consistent to those of a previous article from our center where another screening instrument was used [14].…”
Section: Resultssupporting
confidence: 91%
“…However, in uremia as a chronic disease, in the process of long-term acceptance of PD, there is not only long treatment cycle but also high economic costs. With the progress of treatment, uremia patients undergoing PD will inevitably experience a certain degree of discomfort, which aggravates the physical and psychological burden of patients and further aggravates the complications caused by the disease [ 5 ]. At the same time, the uremia patients who received PD had low confidence in maintenance treatment, and the degree of cooperation with medical staff is not high, and the quality of life and psychological state of the patients are significantly lower than the normal population.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common and significant psychiatric disorder in ESRD patients. The reported prevalence of depression varies from 23% to 46% in patients with ESRD or in dialysis populations 1113. Studies have shown the effect of depression on dialysis, mortality, hospitalization and quality of life in these patients 1416.…”
Section: Introductionmentioning
confidence: 99%